A vorticity stretching diagnostic for turbulent flows - Malm, Johan; Schlatter, Philipp; Sandham, Neil D. (7th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2011, 2011)
Vorticity stretching in wall-bounded turbulent and transitional flows has been investigated by means of a new diagnostic, designed to pick up regions with large amounts of vorticity stretching. It was found that the largest occurrence of vorticity stretching in fully turbulent channel flows is present at a wall-normal distance of y+ = 6.5, i.e. in the transition between the viscous sublayer and the buffer region. Instantaneous data showed that the coherent structures associated with these stretching events have the shape of flat ‘pancake structures’ in the vicinity of high-speed streaks, here denoted ‘h-type’ events. The other event found, also studied in an asymptotic suction boundary layer, is the ‘l-type’ event present on top of an unstable low-speed streak. These events are further thought to be associated with the exponential growth of streamwise vorticity in the turbulent near-wall cycle.
CRIS-Team Scopus Importer:2023-03-21